Climate change, justice and future generations - Page, Edward A. (Cheltenham, 2007)
"Global climate change raises important questions of international and intergenerational justice. In this important new book, the author places research on the origins and impacts of climate change within the broader context of distributive justice and sustainable development. He argues that a range of theories of distribution - notably those grounded in ideals of equality, priority and sufficiency - converge on the adoption of the ambitious global climate policy framework known as 'Contraction and Convergence'. "Climate Change, Justice and Future Generations" will be of great interest to academics and students specialising in environmental ethics, politics and environmental sustainability. It will also be of general interest to those concerned with climate change and the environment."